(untitled) (Comprehensive Journal of Science, 2026)
This research aimed to evaluate the mathematics textbook for third-grade students from the perspective of primary school teachers in Libya. The researcher used the descriptive method as it was suitable for the nature of this research. The research population consisted of (20) primary school mathematics teachers in the city of Zawiya, Libya. The research sample was selected randomly, and it consisted of (11) teachers, representing 55% of the research population. The researcher designed a questionnaire to collect the necessary data for the scientific study. One of the most important findings was that the level of the mathematics textbook for third-grade students, from the perspective of primary school teachers in Libya, was considered to be of an average level.